Participation in Decision Making through E-government Tools: The Case of Valma - Taeeb, Ahmed (My University, 2013)
The progress in information and communication technology (ICT) set high expectations for its effect on the public administration and decision making process. The vision is that the potential of the ICT is able to enhance the public services and provide citizens with efficient tools for effective participation in decision making process. E-government, e-democracy and e-participation are direct results of that ICT progress. Governments were required to apply technology to enhance citizens’ engagement in public policies formulation, which led to create e-participation tools. However, there is a gap between expectations and implementation in many cases. The implementation of these tools face difficulties and challenges that affect their aims of achieving wide citizens engagement and effective influence on public polices. Finland has been one of the leading countries in applying the e-government and e-participation tools on local level. Hence, after couple of decades it is necessary to study whether there is a difference between the vision and implementation. It is important to study how the e-participation tools respond to their users’ needs and expectations. The users’ perspective is essential to arrive at result about the efficiency and effectiveness for these tools in achieving their aims and objectives. The qualitative analysis of the inter-views and the case study of one e-participation tool are used, in order to get in-depth understanding, for the tool efficiency, and the needs and expectations of the users. Valma e-participation tool, provided by the City of Tamper, is one of the tools that are customized for citizens’ participation, on the local level. Valma, as e-participation tool, does not respond sufficiently to the users’ needs and expectations. Valma technological design is insufficient for its purposes of wide engagement and influential participation. Valma lacks the interactivity and possibility to provide citizens with opportunity to post their issues and initiatives. Civil servants do not use Valma widely to post the city issues, because of the low citizens’ participation and institutional rejection which leads to increase the citizens’ disengagement. Citizens’ participation, through Valma, has no influence on the decision making process, due to the low functionality of the tool and the citizens’ low engagement. Valma is unpopular among citizens, which is related to different problems, one of them is the lack of the promotion. Unpopularity of Valma is the main reason of the low citizens’ participation through the tool. The low functionality, distrust and citizens’ low motivation are other reasons of the citizens’ low engagement. However, Valma is easy to use and the language is simplified to be understood for most of the citizens. Valma has different overlapping and dialectically-related problems such as insufficiency of the techno-logical design, citizens’ low participation, non-influence on decision making, and institutional rejection. Valma needs to be developed by taking into consideration the users’ perspective, finding more efficient functions and improving the promotion. Enhancing citizens’ engagement should go beyond applying new technologies, to strengthen the trust and show citizens how their participation makes difference. Improving e-participation tools requires general strategy, efforts and real realization from decision makers.
Keywords: Valma; e-participation tools; e-democracy; e-government; citizens’ engagement; decision making process; fi=Julkisjohtaminen: julkisjohtamisen ohjelma|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|